Izdelava posebnega betona iz metalurških odpadkov težkih kovin - Čop, Rudi (Kovine zlitine tehnologije, 1998)
Presented are practical experiences in manufacturing of special concrete with inclusion of artificial aggregates made from waste materials, occuring during the production or processing of heavy metals. These wastes, dangerous ecological pollutants, are excellent raw materials for production of special concrete. For their manufacturing process an extensive knowledge on the influence of addition of super-plastificators, the velocity of cement hydration process and on the hydraulic volume reduction is required. With a proper selection of artificial aggregates special heavy concrete with wear resistance and specific weight, higher than those from natural aggregates in ordinary concrete, can be made.
Keywords: beton; elektrofiltrski pepel; težke kovine